2014
DOI: 10.3892/etm.2014.2000
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum NDC 75017 alleviates the learning and memory ability in aging rats by reducing mitochondrial dysfunction

Abstract: The aim of the present study was to investigate the protective effect of Lactobacillus plantarum NDC 75017 on D-galactose (D-gal)-induced mitochondrial dysfunction in the rat cerebral cortex. Fifty rats were randomly divided into five groups (n=10 in each group). The rats in the aging model group were subcutaneously injected with 100 mg/kg D-gal and those in the protective groups were additionally orally administered L. plantarum NDC 75017 at doses of 1×108, 1×109 or 1×1010 CFU/100 mg body weight/day, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
3
13
0
1
Order By: Relevance
“…AD is mainly characterized by cognitive deficits. Recent studies have indicated that Lactobacilli and Bifidobacterium improve cognitive deficits in AD patients and model mice . Our previous studies showed that CB treatment could improve depressive‐like behavior and cognitive function .…”
Section: Discussionmentioning
confidence: 99%
“…AD is mainly characterized by cognitive deficits. Recent studies have indicated that Lactobacilli and Bifidobacterium improve cognitive deficits in AD patients and model mice . Our previous studies showed that CB treatment could improve depressive‐like behavior and cognitive function .…”
Section: Discussionmentioning
confidence: 99%
“…Each group of rats were orally administered with L. plantarum MTCC1325 (10 mL/kg body weight) through stainless steel gastric gavage. 13 …”
Section: Methodsmentioning
confidence: 99%
“… 11 , 12 Further, another study reported that L. Plantarum NDC75017 improves the learning and memory ability in aging rats. 13 Previous reports proved that strong antioxidants increases the Na + , K + -ATPases activities by decreasing AChE (Acetyl cholinesterase) levels and improves the cognition by enhancing cholinergic transmission. 14 …”
Section: Introductionmentioning
confidence: 99%
“…In another study Nimgampalle and Kuna revealed that Lactobacillus plantarum MTCC1325 might have anti-Alzheimer properties against D-Galactose induced AD ( 27 ). Further support was provided by Peng et al where they reported that the probiotic bacteria Lactobacillus plantarum NDC75017 improves the learning and memory ability in aging rats ( 37 ). Also Distrutti et al demonstrated that a formulation of probiotic (VSL#3) positively affected inflammatory and neuronal processes and restored impaired synaptic plasticity ( 38 ).…”
Section: Discussionmentioning
confidence: 96%